Causal relationship between telomere length and risk of intracranial aneurysm: a bidirectional Mendelian randomization study - Xu, Bangjie; Ren, Jiangbin; Zhu, Siqi; Ding, Yu; Zhou, Wei; Guo, Qing; Fang, Yan; Zheng, Jing (Frontiers in Neurology, 2024)
Background Telomere length is closely linked to the aging phenotype, where cellular aging results in the production of a cascade of cell factors and the senescence-associated secretory phenotype (SASP), leading to an inflammatory response. The presence of inflammation plays a crucial role in the formation of intracranial aneurysms. Nevertheless, the relationship between telomere length and intracranial aneurysms remains unclear. This study aims to explore the causal connection between telomere length and intracranial aneurysms through the utilization of Mendelian randomization (MR) analysis. Methods Data on telomere length were obtained from the genome-wide association studies conducted on the UK Biobank, comprising a total of 472,174 participants. Data on intracranial aneurysms were obtained from the summary dataset of the Global Genome-wide Association Study (GWAS) conducted by the International Stroke Genetics Consortium. The dataset consisted of 7,495 cases and 71,934 controls, all of European descent. Initially, the linkage disequilibrium score was used to investigate the connection between telomere length and intracranial aneurysms. Subsequently, a bidirectional MR was conducted using two-sample analysis to assess whether there is a causal connection between telomere length and intracranial aneurysm risk. The results were analyzed utilizing five MR methods, with the inverse variance weighted method serving as the main methodology. In addition, we did various analyses to evaluate the presence of heterogeneity, pleiotropy, and sensitivity in the study results. A reverse MR analysis was conducted to investigate potential reverse causal links. Results In the forward MR analysis, it was observed that both the inverse variance-weighted and weighted median analyses implied a potential causal relationship between longer telomere length and a decreased incidence of intracranial aneurysms (IVW: OR = 0.66, 95% CI: 0.47–0.92, p = 1.49 × 10−2). There was no heterogeneity or horizontal pleiotropy. The findings were verified to be robust through the utilization of leave-one-out analysis. The use of reverse MR analysis did not establish a potential causal link between the occurrence of intracranial aneurysms and telomere length. Conclusion There may exist a potential correlation between longer telomere length and a decreased likelihood of intracranial aneurysms within the European population. The present study offers novel insights into the correlation between telomere length and intracranial aneurysms. Additional research is required to clarify the underlying mechanisms and validate our discoveries in diverse populations.